Prevalence of major depression in elder people attending a national hospital in Lima - Matutti, Magnolia (2016)
Objective: To describe, analyze prevalence and predictive risk factors associated with major depression, seniors attended outpatient psychiatric, and uninsured. Material and Methods: 79 elderly uninsured community surrounding Callao to EsSalud, Survey of Drug Consumption applies; and 221 patients with depression and comorbid depression, diagnosed in Psychiatry Clinic. It was used, the Drug Consumption Survey. Results: Demographic factors are independent of depression in both groups (OR = 1.792, 95%CI = 0.573-5.606, age; OR = 1.123, 95%CI = 0.435-4.768, sex; OR = 2.344, 95%CI = 0.325-16.928, health self-perception; OR = 1,905, 95%CI = 0.642 -2.434, depression;, OR = 1. 250, 95%CI = 0.642-2.434, drug use; OR = 1260, 95%CI = 0.763-2.084, disease number). Uninsured comorbid with depression show DM, hypertension, osteoarthritis, and women age 60-75 It is more frequent than in Group 76 more assured, presents qualitative spectrum same trend groups have depression and comorbidity (Figure 1, 2, 3.4) Conclusion: Both groups have depression and comorbidity, even though it is depth analysis needed to confirm data with others.